Understanding child development : for adults who work with young children - Charlesworth, Rosalind (Clifton Park, NY : Thomson/Delmar Learning, 2004)
Intended for preschool and kindergarten teachers, this textbook describes the process of learning, physical and motor growth, toddlers moving towards independence, cognitive growth, and emotional development. The sixth edition adds an appendix of web sites and new material on special needs and more.
Includes bibliographical references
Keywords: Child development